(5-n-Hexyl-2-hydroxymethyl-1,3-dioxan2-yl)methanol - Zhang, M.; Yuan, Xian-You; Ng, S.W. (International Union of Crystallography, 2010)
In the title compound, C12H24O4, the dioxane ring adopts a chair conformation; the n-hexyl chain, which occupies an equatorial position, has an extended zigzag conformation. In the crystal, molecules are connected by O-H center dot center dot center dot O hydrogen-bonds into a zigzag chain running along the b axis, giving rise to a herringbone pattern.